Pemanfaatan Kulit Kakao Adsorben Sebagai Pemurnian Minyak Goreng Bekas - Rini Marlina; Ade Oktasari; Rohmatullaili Rohmatullaili (Stannum : Jurnal Sains dan Terapan Kimia, 2022)
Cooking oil, triglycerides that is liquid at room temperature, is one of important foodstuffs. Repeated use of cooking oil might decrease the quality of the oil and leads to negative impacts on health. An alternative method to treat used cooking oil is adsorption with cacao shell. This present study aims to find out the influences of adsorbent and size variation of cacao peels as the adsorbent on the reduction of free fatty acid, peroxide numbers and water content in used cooking oil. The test parameters of this study were the reduction of free fatty acids by alkalimetric titration; peroxide number by iodometric titration; and content of water by oven-drying method. In the present study, cacao nibs were used as an absorbent to reduce the levels of free fatty acid, water, and peroxide number with variety sizes of the particle, such as 100 mesh and 120 mesh: and 8-hour contact time. The results of the present study indicated a decrease in free fatty acid from 0,448% to 0,327% dan 0,278%; the initial water content of 0,020% decreased to 0,010% and 0,009%; the peroxide number changed from 15,3 meq O2/kg to 3,25 meq O2/kg and 1,25 meq O2/kg. Based on the results, the absorbent that has the optimum adsorption is the 120 mesh particle size of adsorbent.